Flash Card Media Analysis of Wudhu Learning for Autistic Children - Erna Rochmawati; Eni Fariatul Fahyuni (Universitas Muhammadiyah Sidoarjo, 2022)
Flash card media is an illustrated media that contains image patches to attract learning interest for children with special needs, including children with autism at PKBL Lentera Fajar Indonesia is a homeschooling institution that provides learning service for children with special needs using various learning media, one of them is flash card media for learning ablution. The subject of this study were 3 autistic children. The purpose of this study was to describe the application of flash card media with ablution material of autistic children at the Lentera Fajar Indonesia PKBM Institude, to determine the inhibiting factors in learning for autistic children at the Lentera Fajar Indonesia PKBM Institude. For teachers learning with flash card media is a medium that is easy to find, easy to make, while for children it is to be able to attract interest in learning by looking at the pictures contained on flash card. The results showed that the learning process with the application of flash card media was able to attract autistic children about learning ablution and did not forget to help facilitate therapist teachers in delivering ablution material.